Innovative health service delivery models in low and middle income countries - what can we learn from the private sector? - Daar Abdallah S; Dunne David; McGahan Anita; Khor Sara; Bhattacharyya Onil; Singer Peter A (BMC, 2010)
Abstract Background The poor in low and middle income countries have limited access to health services due to limited purchasing power, residence in underserved areas, and inadequate health literacy. This produces significant gaps in health care delivery among a population that has a disproportionately large burden of disease. They frequently use the private health sector, due to perceived or actual gaps in public services. A subset of private health organizations, some called social enterprises, have developed novel approaches to increase the availability, affordability and quality of health care services to the poor through innovative health service delivery models. This study aims to characterize these models and identify areas of innovation that have led to effective provision of care for the poor. Methods An environmental scan of peer-reviewed and grey literature was conducted to select exemplars of innovation. A case series of organizations was then purposively sampled to maximize variation. These cases were examined using content analysis and constant comparison to characterize their strategies, focusing on business processes. Results After an initial sample of 46 studies, 10 case studies of exemplars were developed spanning different geography, disease areas and health service delivery models. These ten organizations had innovations in their marketing, financing, and operating strategies. These included approaches such a social marketing, cross-subsidy, high-volume, low cost models, and process reengineering. They tended to have a narrow clinical focus, which facilitates standardizing processes of care, and experimentation with novel delivery models. Despite being well-known, information on the social impact of these organizations was variable, with more data on availability and affordability and less on quality of care. Conclusions These private sector organizations demonstrate a range of innovations in health service delivery that have the potential to better serve the poor's health needs and be replicated. There is a growing interest in investing in social enterprises, like the ones profiled here. However, more rigorous evaluations are needed to investigate the impact and quality of the health services provided and determine the effectiveness of particular strategies.